2012
DOI: 10.5430/afr.v1n2p87
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perceived Stress and Facebook on Accounting Students’ Academic Performance

Abstract: This paper has three objectives. First, we investigate the effects of perceived stress on the academic performance of accounting students. Second, we examine the association of Facebook use with perceived stress. Third, we investigate the effect of Facebook usage on accounting students' academic performance. To measure the perceived stress we used the Perceived Stress Scale developed in the prior research for the shorter version and used it to collect data from accounting students at two universities. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 36 publications
2
30
2
5
Order By: Relevance
“…There are several limited studies have been done to determine the relationship between Facebook addiction with psychological factors such as depression, anxiety and stress (Aker, Sahin, Sezgin, & Oguz, 2017;Labrague, 2014). The study by Gabre and Kumar (2012) among African-American accounting students found stress to be related with Facebook use. Similar to what we had observed, Labrague (2014) and Brailovskaia and Margraf (2017) also noted a correlation between Facebook use and the levels of depression, anxiety and stress.…”
Section: Ijphcsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several limited studies have been done to determine the relationship between Facebook addiction with psychological factors such as depression, anxiety and stress (Aker, Sahin, Sezgin, & Oguz, 2017;Labrague, 2014). The study by Gabre and Kumar (2012) among African-American accounting students found stress to be related with Facebook use. Similar to what we had observed, Labrague (2014) and Brailovskaia and Margraf (2017) also noted a correlation between Facebook use and the levels of depression, anxiety and stress.…”
Section: Ijphcsmentioning
confidence: 99%
“…Stress is defined by DSM-5 criteria as a state of being worried/ overwhelmed thus leading to psychological health issues (American Psychiatric Association, 2013). It has been reported that students indulge in social networking applications such as Facebook, to escape the levels of stress (Ching et al, 2017;Gabre & Kumar, 2012).…”
Section: Ijphcsmentioning
confidence: 99%
“…Os autores não só investigaram os efeitos desse fenômeno sobre o desempenho acadêmico dos estudantes de contabilidade, como também examinaram a associação do uso do Facebook com o stress percebido e a sua influência sobre o desempenho acadêmico desses discentes. Como medida, foi aplicada a Escala de Stress Percebido (PSS), revelando os resultados que estudantes de contabilidade afro-americanos eram mais propensos a relatar escores de stress superiores em comparação aos estudantes americanos não africanos e, finalmente, estudantes que usaram o Facebook, enquanto estudavam, obtiveram desempenho acadêmico inferior (Gabre & Kumar, 2012).…”
Section: Desempenho Acadêmicounclassified
“…It is indubitable that educational engagements with social media can be one of the most beneficial things for many school students because it can be used for efficient and effective learning (Brooks, 2015;Crittenden, Hopkins, & Simmons, 2011;Terblanche, 2011). At the same time, these activities can create a different kind of stressful and adverse situations for the students (Brodmerkel & Carah, 2013;Gabre & Kumar, 2012). Cyberbullying is one of the harmful factors that student usually faces in the online environment.…”
Section: Introductionmentioning
confidence: 99%